(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Dual education of professional education integrative macro environment theoretical aspect based on The importance of resources in dual education is emphasized. The integrative macroenvironment of professional education is characterized by the features of integrativeness, discreteness, genealogy, integrity, variability, intensity.